2013
DOI: 10.1179/1753614613z.00000000036
|View full text |Cite
|
Sign up to set email alerts
|

Midline back pain: A literature review

Abstract: Aim: To find out what is known about midline back pain. Method: Literature search. Results: Midline back pain was found to be as distinctive a concept as peripheral sciatica, and yet pain drawing analyses often lacked a midline pain category. Furthermore, the element of axial symmetry was seldom inspected. There were few studies of clinical tests provoking midline pain responses and a paucity of statistical analysis to elucidate the modes of clinical presentation of midline back pain. Some clinical studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…1 A review of the literature revealed a lack of statistical analysis of the meaning of pain being felt or induced in the midline of the back. 2 Therefore, a database inspection of this midline aspect of back pain is presented.…”
Section: Introductionmentioning
confidence: 99%
“…1 A review of the literature revealed a lack of statistical analysis of the meaning of pain being felt or induced in the midline of the back. 2 Therefore, a database inspection of this midline aspect of back pain is presented.…”
Section: Introductionmentioning
confidence: 99%